(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper revisits two graffiti from the Roman city of Pollentia (Alcúdia, Majorca) and one of the legends of a group of locally issued coin-shaped lead tokens. The three inscriptions were previously regarded as Iberian, but in all probability they are Latin. The graffiti seem to be indications of ownership, one containing a name of Punic origin and the other a Latin name, whereas the reading of the legends is very doubtful. The study also discusses a lead tablet of unknown provenance bearing a text that has been regarded as Iberian. There can be no doubt that it is a modern forgery.